2013
DOI: 10.1074/jbc.m113.449926
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Chemokine Receptor Signaling Induces Apoptosis in Acute Myeloid Leukemia Cells via Regulation of the Bcl-2 Family Members Bcl-XL, Noxa, and Bak

Abstract: Background:The chemokine receptor CXCR4 plays a role in AML. Results: SDF-1, the ligand of CXCR4, induces apoptosis in AML cell lines and patient samples via modulation of Bcl-2 family members. Conclusion: SDF-1 induces apoptosis of AML cells via up-regulation of Bak and Noxa and down-regulation of Bcl-X L . Significance: SDF-1/CXCR4 signaling could induce AML cell apoptosis if bone marrow survival cues can be disrupted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 68 publications
(49 reference statements)
6
72
0
Order By: Relevance
“…The human bone marrowderived tert-immortalized bone marrow stromal cell line (t-BMSC) (31) was a gift from Dario Campana (St. Jude, Memphis, TN) and was maintained as described (8). The CXCR4-expressing KG1a cells (KG1a-CXCR4) were generated via transient transfection of a plasmid encoding a CXCR4-YFP fluorescent fusion protein (32) into the AML cell line KG1a (ATCC), as previously described (10).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The human bone marrowderived tert-immortalized bone marrow stromal cell line (t-BMSC) (31) was a gift from Dario Campana (St. Jude, Memphis, TN) and was maintained as described (8). The CXCR4-expressing KG1a cells (KG1a-CXCR4) were generated via transient transfection of a plasmid encoding a CXCR4-YFP fluorescent fusion protein (32) into the AML cell line KG1a (ATCC), as previously described (10).…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that AML patient isolates and cell lines expressing high levels of CXCR4 underwent apoptosis in response to treatment with SDF-1 (10). Preliminary studies conducted predominantly in AML cell lines also suggested that osteoblasts protect AML cells expressing high levels of CXCR4 from this SDF-1-induced apoptosis (8).…”
Section: Osteoblasts Protect Aml Isolates From Apoptosis In a Co-cultmentioning
confidence: 99%
See 3 more Smart Citations